Conductive coating for carbon-coated aluminum foil
By combining modified polyacrylic acid with conductive carbon black, graphene, silver powder and other materials, a dynamic cross-linked network is formed, which solves the problem of easy coating breakage during the processing of carbon-coated aluminum foil and improves the energy density and service life of lithium-ion batteries.
Patent Information
- Application Number
- CN202511022661.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-24
- Publication Date
- 2025-10-17
AI Technical Summary
Currently, the surface coating of carbon-coated aluminum foil is prone to breakage and damage during processing, which affects the normal use of lithium-ion batteries and the volumetric energy density of the batteries.
By using modified polyacrylic acid and conductive carbon black, few-layer graphene, silver powder and polyvinylpyrrolidone as raw materials, a dynamic cross-linked network is formed through the preparation of modified monomers and modifiers, which enhances the mechanical properties of the coating and ensures the battery energy density and adhesion at low thickness.
By reducing the coating thickness, the energy density of the lithium-ion battery is increased, the coating is prevented from cracking during welding, and the battery life and adhesion are improved.
Smart Images

Figure BDA0005515031700000111
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of conductive coating preparation, in particular to a conductive coating for carbon-coated aluminum foil. BACKGROUND
[0002] Lithium ion batteries are widely used in different fields such as digital products, power, energy storage, etc. due to their high energy density, high voltage, wide operating temperature range, no memory effect, good cycle performance and long service life. However, lithium batteries have poor conductivity, low rate performance and poor heat dissipation performance, which affects their further application. Lithium ion batteries commonly use aluminum foil or carbon-coated aluminum foil as the carrier of the positive material. Coating a conductive carbon layer on the surface of the aluminum foil can inhibit battery polarization, reduce thermal effects and improve the rate performance of the battery. However, the thickness of the coating on the surface of the carbon-coated aluminum foil at the present stage is too thick, which will affect the volume energy density of the battery. In order to increase the volume energy density of the battery, the thickness of the conductive coating on the carbon-coated aluminum foil is reduced. The reduced coating will be damaged during processing or welding, resulting in surface coating cracking and affecting the normal use of the battery. SUMMARY
[0003] The present application relates to the technical field of conductive coating preparation, in particular to a conductive coating for carbon-coated aluminum foil.
[0004] The object of the present application can be achieved by the following technical solutions:
[0005] A conductive coating for carbon-coated aluminum foil is prepared by the following steps:
[0006] Step A1: uniformly mix acrylic acid, diethanolamine, p-toluenesulfonic acid, hydroquinone and DMF, and protect it with nitrogen. React at a speed of 120-150 r / min and a temperature of 80-85℃ for 2-3h to obtain intermediate 1. Uniformly mix intermediate 1, mercaptoacetic acid, p-toluenesulfonic acid and DMF, and react at a speed of 200-300 r / min and a temperature of 110-115℃ for 6-8h to obtain a modifier.
[0007] Step A2: uniformly mix acrylic acid, acrylamide and acrylonitrile, and stir at a speed of 150-200 r / min and a temperature of 70-80℃. Add azobisisobutyronitrile and react for 15-20min. Then add the modified monomer and continue to react for 2-4h. Adjust the pH value to 6-6.5 to obtain pretreated polyacrylic acid. Uniformly mix the pretreated polyacrylic acid, the modifier and chloroplatinic acid, and react at a speed of 200-300 r / min and a temperature of 75-85℃ for 6-8h to obtain modified polyacrylic acid.
[0008] Step A3: Weigh the following raw materials in parts by weight: 3-10 parts of conductive carbon black, 90-97 parts of few-layer graphene, 100-150 parts of modified polyacrylic acid, 3-5 parts of silver powder, 15-30 parts of polyvinyl pyrrolidone and 500-1500 parts of solvent, mix the raw materials evenly, and prepare a carbon-coated aluminum foil conductive coating.
[0009] Furthermore, in the preparation of the intermediate 1 described in step A1, the molar ratio of acrylic acid to diethanolamine is 1:1, the amount of p-toluenesulfonic acid is 1% by mass of the ethylene glycolamine, and the amount of hydroquinone is 1‰ by mass of the ethylene glycolamine. In the preparation of the modifier, the molar ratio of the intermediate 1 to thioglycolic acid is 1:2, and the amount of p-toluenesulfonic acid is 1.5% by mass of the intermediate 1.
[0010] Furthermore, the weight ratio of acrylic acid, acrylamide, acrylonitrile and modified monomer described in step A2 is 60-70:20-30:10-15:2-4, the amount of azobisisobutyronitrile is 3‰ of the sum of the mass of acrylic acid, acrylamide and acrylonitrile, the molar ratio of Si-H bonds on the pretreated acrylic acid and the modifier is 1:1, and the amount of chloroplatinic acid and is 1‰ of the mass of the modifier.
[0011] Furthermore, the number of layers of the few-layer graphene described in step A3 is 2-10 layers, the particle size is less than 10 μm, the silver powder particle size is 3 μm, the model of polyvinyl pyrrolidone is K30, and the solvent is a mixture of deionized water and alcohol in any proportion, and the alcohol is a mixture of one or more of ethanol, n-propanol, isopropanol and n-butanol in any proportion.
[0012] Furthermore, the modified monomer is prepared by the following steps:
[0013] Step B1: p-phenylenediamine, allyl alcohol glycidyl ether, and DMF are mixed and reacted at a speed of 120-150 r / min, a temperature of 60-70°C, and a pH of 11-12 for 3-5 hours to obtain intermediate 2. Intermediate 2, p-nitrophenylboric acid, and DMF are mixed and nitrogen is passed through the mixture. The reaction is carried out at a speed of 150-200 r / min, a temperature of 110-115°C, and a pH of 7.5-8 for 3-5 hours to obtain intermediate 3.
[0014] Step B2: Intermediate 3, trichlorosilane, chloroplatinic acid and DMF are mixed uniformly, nitrogen protection is introduced, and the reaction is carried out at a speed of 200-300 r / min and a temperature of 75-85°C for 6-8 hours to obtain intermediate 4. Dimethylhydrogen silicon alkoxide lithium and DMF are mixed, and trifluoropropylmethylcyclotrisiloxane is added at a speed of 150-200 r / min and a temperature of 0°C. The mixture is heated to 25-30°C and reacted for 20-24 hours. A modifier is added and the reaction is continued for 1-1.5 hours to obtain modified polysiloxane;
[0015] Step B3: mixing the modified polysiloxane, zinc powder, deionized water and DMF uniformly, stirring at a rotation speed of 60-80 r / min and a temperature of 90-95℃, adding concentrated hydrochloric acid and reacting for 3-4 h to obtain aminosilicone, mixing the aminosilicone, p-toluenesulfonic acid, 4A molecular sieve and DMF uniformly, stirring at a rotation speed of 300-500 r / min and a temperature of 50-60℃, adding cinnamyl aldehyde and reacting for 5-7 h to obtain a modified monomer.
[0016] Further, the molar ratio of the p-phenylenediamine and allyl glycidyl ether in step B1 is 1:4, and the molar ratio of the intermediate 2 and p-nitrophenylboronic acid is 1:2.
[0017] Further, the molar ratio of the intermediate 3 and trichlorosilane in step B2 is 1:4, the amount of chloroplatinic acid is 1 ‰ of the mass of trichlorosilane, and the molar ratio of dimethylhydrosilicon lithium, trifluoropropylmethylcyclotrisiloxane and Si-Cl on the intermediate 4 is 1:5:1.
[0018] Further, the amount ratio of the modified polysiloxane, zinc powder, deionized water, DMF and concentrated hydrochloric acid in step B3 is 152 g:15 g:50 mL:200 mL:50 mL, the mass fraction of concentrated hydrochloric acid is 36%, the molar ratio of the amino group on the aminosilicone and cinnamyl aldehyde is 1:1, and the amount of p-toluenesulfonic acid is 1%.
[0019] The conductive coating for carbon-coated aluminum foil prepared by the method has the following raw materials: conductive carbon black, few-layer graphene, modified polyacrylic acid, silver powder, polyvinylpyrrolidone and solvent, the modified polyacrylic acid is prepared by using acrylic acid and diethanolamine as raw materials, dehydrating the carboxyl group on the acrylic acid and the secondary amine on the diethanolamine to obtain an intermediate 1, reacting the intermediate 1 with mercaptoacetic acid to make the hydroxyl group on the intermediate 1 react with the carboxyl group on the mercaptoacetic acid to obtain a modifier, polymerizing acrylic acid, acrylamide, acrylonitrile and the modified monomer to obtain pretreated polyacrylic acid, and making the Si-H bond on the pretreated polyacrylic acid react with the double bond on the modifier under the action of chloroplatinic acid to obtain modified polyacrylic acid.
[0020] The modified monomer is prepared by using p-phenylenediamine and allyl glycidyl ether as raw materials, reacting the amino group on the p-phenylenediamine with the epoxy group on the allyl glycidyl ether to form a hydroxyl group, obtaining an intermediate 2, reacting the intermediate 2 with p-nitrophenylboronic acid, and reacting the diol on the intermediate 2 with the boric acid on the p-nitrophenylboronic acid to form a borate structure, obtaining an intermediate 3, reacting the intermediate 3 with trichlorosilane, and reacting the double bond on the intermediate 3 with the Si-H bond on the trichlorosilane, obtaining an intermediate 4, using dimethyl hydrogen silanol lithium as an initiator, using trifluoropropylmethylcyclotrisiloxane as a polymerization monomer, and adding a modifier, and reacting the Si-Cl on the modifier with the silanol lithium, obtaining a modified polysiloxane, reducing the modified polysiloxane with zinc powder, converting the nitro group on the modified polysiloxane into an amino group, obtaining an aminated polysiloxane, and reacting the aminated polysiloxane with cinnamaldehyde, reacting the amino group on the aminated polysiloxane with the aldehyde group on the cinnamaldehyde to form an imine structure, and obtaining the modified monomer.
[0021] During the coating drying process, the modified polyacrylic acid molecules can form a coordination bond with the silver ions of the silver powder, thereby strengthening the contact between the silver powder and the modified polyacrylic acid, helping to form a conductive path. During the preparation of the modified polyacrylic acid, a modified monomer is added to form a dynamic crosslinking network of the modified polyacrylic acid molecules, thereby increasing the mechanical properties of the coating and reducing the thickness of the coating. In the case of low thickness, the coating film still guarantees the function, thereby improving the energy density of the battery. Moreover, the surface coating is not prone to cracking during the welding process of the carbon-coated aluminum foil. The organic silicon segment and fluorine element contained in the modified polyacrylic acid molecules can inhibit the penetration of the electrolyte, ensuring the adhesion of the coating, and the coating does not fall off after multiple cycles of the battery, thereby increasing the service life of the battery. DETAILED DESCRIPTION
[0022] The technical solutions in the embodiments of the present application will be described below in a clear and complete manner. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those of ordinary skill in the art without creative labor fall within the scope of protection of the present application.
[0023] Embodiment 1, a conductive coating for carbon-coated aluminum foil, is prepared by the following steps:
[0024] Step A1: uniformly mix acrylic acid, diethanolamine, p-toluenesulfonic acid, hydroquinone, and DMF, protect under nitrogen, and react at a rotation speed of 120 r / min and a temperature of 80℃ for 2 h to obtain an intermediate 1. Uniformly mix the intermediate 1, mercaptoacetic acid, p-toluenesulfonic acid, and DMF, and react at a rotation speed of 200 r / min and a temperature of 110℃ for 6 h to obtain a modifier;
[0025] Step A2: uniformly mix acrylic acid, acrylamide, acrylonitrile and DMF, stir at a rotation speed of 150 r / min and a temperature of 70℃, and add azobisisobutyronitrile, react for 15 min, then add the modified monomer, continue to react for 2 h, adjust the pH value to 6, and prepare a pretreated polyacrylic acid; uniformly mix the pretreated polyacrylic acid, the modifier, chloroplatinic acid and DMF, and react for 6 h at a rotation speed of 200 r / min and a temperature of 75℃ to prepare modified polyacrylic acid;
[0026] Step A3: weigh the following raw materials: 3 parts of conductive carbon black, 90 parts of few-layer graphene, 100 parts of modified polyacrylic acid, 3 parts of silver powder, 15 parts of polyvinylpyrrolidone and 500 parts of solvent, uniformly mix the raw materials, and prepare a conductive coating for carbon-coated aluminum foil.
[0027] In the preparation of the intermediate 1 in step A1, the molar ratio of acrylic acid to diethanolamine is 1:1, the amount of p-toluenesulfonic acid is 1% of the mass of diethanolamine, and the amount of hydroquinone is 1‰ of the mass of diethanolamine; in the preparation of the modifier, the molar ratio of intermediate 1 to mercaptoacetic acid is 1:2, and the amount of p-toluenesulfonic acid is 1.5% of the mass of intermediate 1.
[0028] In step A2, the weight ratio of acrylic acid, acrylamide, acrylonitrile and modified monomer is 60:20:10:2, the amount of azobisisobutyronitrile is 3‰ of the sum of the masses of acrylic acid, acrylamide and acrylonitrile, the molar ratio of Si-H bonds on the pretreated acrylic acid to the modifier is 1:1, and the amount of chloroplatinic acid is 1‰ of the mass of the modifier.
[0029] In step A3, the number of layers of the few-layer graphene is 2, the particle size is 8 μm, the particle size of the silver powder is 3 μm, the type of polyvinylpyrrolidone is K30, and the mass ratio of the deionized water, ethanol and n-propanol mixed as the solvent is 10:8:3.
[0030] The modified monomer is prepared by the following steps:
[0031] Step B1: mix p-phenylenediamine, allyl glycidyl ether and DMF, react at a rotation speed of 120 r / min, a temperature of 60℃ and a pH value of 11 for 3 h to prepare intermediate 2, mix intermediate 2, p-nitrophenylboronic acid and DMF, protect with nitrogen, react at a rotation speed of 150 r / min, a temperature of 110℃ and a pH value of 7.5 for 3 h, and prepare intermediate 3;
[0032] Step B2: Intermediate 3, trichlorosilane, chloroplatinic acid and DMF were mixed uniformly, protected by nitrogen, stirred at 200 r / min and 75℃ for 6h, then lithium dimethylhydrosilanol and DMF were mixed, stirred at 150 r / min and 0℃, then trifluoropropylmethylcyclotrisiloxane was added, heated to 25℃ and reacted for 20h, then the modifier was added and reacted for 1h to obtain the modified polysiloxane;
[0033] Step B3: The modified polysiloxane, zinc powder, deionized water and DMF were mixed uniformly, stirred at 60 r / min and 90℃, then concentrated hydrochloric acid was added and reacted for 3h to obtain the aminated polysiloxane, then the aminated polysiloxane, p-toluenesulfonic acid and 4A molecular sieve and DMF were mixed uniformly, stirred at 300 r / min and 50℃, then cinnamyl aldehyde was added and reacted for 5h to obtain the modified monomer.
[0034] The molar ratio of the p-phenylenediamine and allyl glycidyl ether in step B1 was 1:4, and the molar ratio of intermediate 2 and p-nitrophenylboronic acid was 1:2.
[0035] The molar ratio of intermediate 3 and trichlorosilane in step B2 was 1:4, the amount of chloroplatinic acid was 1‰ of the mass of trichlorosilane, and the molar ratio of lithium dimethylhydrosilanol, trifluoropropylmethylcyclotrisiloxane and Si-Cl on intermediate 4 was 1:5:1.
[0036] The amount ratio of the modified polysiloxane, zinc powder, deionized water, DMF and concentrated hydrochloric acid in step B3 was 152g:15g:50mL:200mL:50mL, the mass fraction of concentrated hydrochloric acid was 36%, the molar ratio of amino on the aminated polysiloxane and cinnamyl aldehyde was 1:1, and the amount of p-toluenesulfonic acid was 1%.
[0037] Example 2, a conductive coating for carbon-coated aluminum foil, was prepared by the following steps:
[0038] Step A1: Acrylic acid, diethanolamine, p-toluenesulfonic acid, hydroquinone and DMF were mixed uniformly, protected by nitrogen, and reacted at 120 r / min and 85℃ for 2h to obtain intermediate 1, then intermediate 1, mercaptoacetic acid, p-toluenesulfonic acid and DMF were mixed uniformly, reacted at 300 r / min and 113℃ for 7h to obtain the modifier.
[0039] Step A2: uniformly mix acrylic acid, acrylamide, acrylonitrile and DMF, stir at a rotation speed of 150 r / min and a temperature of 75℃, and add azobisisobutyronitrile, react for 18 min, then add the modified monomer, continue to react for 3 h, adjust the pH value to 6.5, and prepare a pretreated polyacrylic acid; uniformly mix the pretreated polyacrylic acid, the modifier, chloroplatinic acid and DMF, and react at a rotation speed of 200 r / min and a temperature of 80℃ for 7 h to prepare a modified polyacrylic acid;
[0040] Step A3: weigh the following raw materials: 6 parts of conductive carbon black, 93 parts of few-layer graphene, 125 parts of modified polyacrylic acid, 4 parts of silver powder, 23 parts of polyvinylpyrrolidone and 1000 parts of solvent, uniformly mix the raw materials, and prepare a conductive coating for carbon-coated aluminum foil.
[0041] In the preparation of the intermediate 1 in step A1, the molar ratio of acrylic acid to diethanolamine is 1:1, the amount of p-toluenesulfonic acid is 1% of the mass of diethanolamine, and the amount of hydroquinone is 1‰ of the mass of diethanolamine; in the preparation of the modifier, the molar ratio of intermediate 1 to mercaptoacetic acid is 1:2, and the amount of p-toluenesulfonic acid is 1.5% of the mass of intermediate 1.
[0042] In step A2, the weight ratio of acrylic acid, acrylamide, acrylonitrile and modified monomer is 65:25:12:3, the amount of azobisisobutyronitrile is 3‰ of the sum of the masses of acrylic acid, acrylamide and acrylonitrile, the molar ratio of Si-H bonds on the pretreated acrylic acid to the modifier is 1:1, and the amount of chloroplatinic acid is 1‰ of the mass of the modifier.
[0043] In step A3, the number of layers of the few-layer graphene is 5, the particle size of the silver powder is 3 μm, the type of polyvinylpyrrolidone is K30, and the mass ratio of the solvents deionized water, ethanol, n-propanol and isopropanol is 15:3:3:1.
[0044] The modified monomer is prepared by the following steps:
[0045] Step B1: mix p-phenylenediamine, allyl glycidyl ether and DMF, react at a rotation speed of 120 r / min, a temperature of 65℃ and a pH value of 12 for 4 h to prepare intermediate 2, mix intermediate 2, p-nitrophenylboronic acid and DMF, protect with nitrogen, react at a rotation speed of 150 r / min, a temperature of 113℃ and a pH value of 8 for 4 h, and prepare intermediate 3;
[0046] Step B2: Intermediate 3, trichlorosilane, chloroplatinic acid and DMF were mixed uniformly, protected by nitrogen, stirred at 200 r / min and 80℃ for 7h, then lithium dimethylhydrosilanol and DMF were mixed, stirred at 150 r / min and 0℃, then trifluoropropylmethylcyclotrisiloxane was added, heated to 28℃, stirred for 22h, then the modifier was added, and stirred for 1.3h to obtain the modified polysiloxane.
[0047] Step B3: The modified polysiloxane, zinc powder, deionized water and DMF were mixed uniformly, stirred at 60 r / min and 93℃, then concentrated hydrochloric acid was added, and stirred for 3.5h to obtain the aminated polysiloxane. The aminated polysiloxane, p-toluenesulfonic acid and 4A molecular sieve and DMF were mixed uniformly, stirred at 300 r / min and 55℃, then cinnamaldehyde was added, and stirred for 6h to obtain the modified monomer.
[0048] The molar ratio of the p-phenylenediamine and allyl glycidyl ether in step B1 was 1:4, and the molar ratio of intermediate 2 and p-nitrophenylboronic acid was 1:2.
[0049] The molar ratio of intermediate 3 and trichlorosilane in step B2 was 1:4, and the amount of chloroplatinic acid was 1‰ of the mass of trichlorosilane. The molar ratio of lithium dimethylhydrosilanol, trifluoropropylmethylcyclotrisiloxane and Si-Cl on intermediate 4 was 1:5:1.
[0050] The amount ratio of the modified polysiloxane, zinc powder, deionized water, DMF and concentrated hydrochloric acid in step B3 was 152g:15g:50mL:200mL:50mL, the mass fraction of concentrated hydrochloric acid was 36%, and the molar ratio of amino on the aminated polysiloxane and cinnamaldehyde was 1:1. The amount of p-toluenesulfonic acid was 1%.
[0051] Example 3, a conductive coating for carbon-coated aluminum foil, was prepared by the following steps:
[0052] Step A1: Acrylic acid, diethanolamine, p-toluenesulfonic acid, hydroquinone and DMF were mixed uniformly, protected by nitrogen, stirred at 150 r / min and 85℃ for 3h to obtain intermediate 1. Intermediate 1, mercaptoacetic acid, p-toluenesulfonic acid and DMF were mixed uniformly, stirred at 300 r / min and 115℃ for 8h to obtain the modifier.
[0053] Step A2: acrylic acid, acrylamide, acrylonitrile and DMF were mixed uniformly, azobisisobutyronitrile was added under the condition of 200 r / min and 80℃, after 20 min, the modified monomer was added and reacted for 4 h, the pH value was adjusted to 6.5, and the pretreated polyacrylic acid was prepared; the pretreated polyacrylic acid, modifier, chloroplatinic acid and DMF were mixed uniformly, and reacted for 8 h under the condition of 300 r / min and 85℃, and the modified polyacrylic acid was prepared;
[0054] Step A3: the raw materials were weighed as follows: 10 parts of conductive carbon black, 97 parts of few-layer graphene, 150 parts of modified polyacrylic acid, 5 parts of silver powder, 30 parts of polyvinylpyrrolidone and 1500 parts of solvent, and the raw materials were mixed uniformly to prepare a conductive coating for carbon-coated aluminum foil.
[0055] In the preparation of the intermediate 1 in step A1, the molar ratio of acrylic acid to diethanolamine was 1:1, the amount of p-toluenesulfonic acid was 1% of the mass of diethanolamine, and the amount of hydroquinone was 1‰ of the mass of diethanolamine; in the preparation of the modifier, the molar ratio of intermediate 1 to mercaptoacetic acid was 1:2, and the amount of p-toluenesulfonic acid was 1.5% of the mass of intermediate 1.
[0056] In step A2, the weight ratio of acrylic acid, acrylamide, acrylonitrile and modified monomer was 70:30:15:4, the amount of azobisisobutyronitrile was 3‰ of the sum of the mass of acrylic acid, acrylamide and acrylonitrile, the molar ratio of Si-H bond on the pretreated acrylic acid to the modifier was 1:1, and the amount of chloroplatinic acid was 1% of the mass of the modifier.
[0057] In step A3, the number of layers of the few-layer graphene was 10, the particle size was 8 μm, the particle size of the silver powder was 3 μm, the type of polyvinylpyrrolidone was K30, and the mass ratio of the solvents deionized water, ethanol, n-propanol, isopropanol and n-butanol was 10:5:2:2:1.
[0058] The modified monomer was prepared by the following steps:
[0059] Step B1: p-phenylenediamine, allyl glycidyl ether and DMF were mixed, and reacted for 5 h under the condition of 150 r / min, 70℃ and pH 12 to prepare intermediate 2; intermediate 2, p-nitrophenylboronic acid and DMF were mixed, and protected by nitrogen, and reacted for 5 h under the condition of 200 r / min, 115℃ and pH 8 to prepare intermediate 3;
[0060] Step B2: Intermediate 3, trichlorosilane, chloroplatinic acid and DMF were mixed uniformly, protected by nitrogen, stirred at 300 r / min and 85℃ for 8h, then lithium dimethylhydrosilanol and DMF were mixed, stirred at 200 r / min and 0℃, then trifluoropropylmethylcyclotrisiloxane was added, heated to 30℃ and reacted for 24h, then the modifier was added and reacted for 1.5h to obtain the modified polysiloxane;
[0061] Step B3: The modified polysiloxane, zinc powder, deionized water and DMF were mixed uniformly, stirred at 80 r / min and 95℃, then concentrated hydrochloric acid was added and reacted for 4h to obtain the aminated polysiloxane, then the aminated polysiloxane, p-toluenesulfonic acid and 4A molecular sieve and DMF were mixed uniformly, stirred at 500 r / min and 60℃, then cinnamyl aldehyde was added and reacted for 7h to obtain the modified monomer.
[0062] The molar ratio of p-phenylenediamine to allyl glycidyl ether in step B1 was 1:4, and the molar ratio of intermediate 2 to p-nitrophenylboronic acid was 1:2.
[0063] The molar ratio of intermediate 3 to trichlorosilane in step B2 was 1:4, and the amount of chloroplatinic acid was 1‰ of the mass of trichlorosilane. The molar ratio of dimethylhydrosilanol, trifluoropropylmethylcyclotrisiloxane and Si-Cl on intermediate 4 was 1:5:1.
[0064] The amount ratio of modified polysiloxane, zinc powder, deionized water, DMF and concentrated hydrochloric acid in step B3 was 152g:15g:50mL:200mL:50mL, the mass fraction of concentrated hydrochloric acid was 36%, the molar ratio of amino on aminated polysiloxane to cinnamyl aldehyde was 1:1, and the amount of p-toluenesulfonic acid was 1%.
[0065] Comparative Example 1: This comparative example was the same as Example 1 except that silver powder was not added.
[0066] Comparative Example 2: This comparative example was the same as Example 1 except that hexamethylcyclotrisiloxane was used instead of trifluoropropylmethylcyclotrisiloxane.
[0067] Comparative Example 3: This comparative example was the same as Example 1 except that modified polysiloxane was used instead of modified monomer.
[0068] The conductive coating prepared from Examples 1-3 and Comparative Examples 1-3 was tested according to GB / T6739-2006 "Paints and varnishes - Determination of film hardness by pencil test"; the adhesion was tested according to GB / T5210-2006 "Paints and varnishes - Pull-off test for adhesion - Method using a single test column from one side" on the coated test panel; the flexibility was tested according to GB / T1731-2020 "Determination of flexibility of paint film, putty film", the smaller the value, the better the flexibility of the coating, and the test results are shown in Table 1.
[0069] Table 1
[0070]
[0071]
[0072] From Table 1, it can be seen that the present application has good mechanical properties and can meet the use requirements of carbon-coated aluminum foil.
[0073] The above content is only an example and description of the concept of the present application. Those skilled in the art can make various modifications or supplements to the described specific embodiments or use similar ways to replace them, as long as they do not deviate from the concept of the present application or exceed the scope defined by the present claims, and they should belong to the protection scope of the present application.
Claims
1. A carbon-coated aluminum foil conductive coating, characterized by: Made by the following steps: Step A1: acrylic acid, diethanolamine, p-toluenesulfonic acid, hydroquinone, and DMF are uniformly mixed and reacted under nitrogen protection to obtain intermediate 1. Intermediate 1, thioglycolic acid, p-toluenesulfonic acid, and DMF are mixed and reacted to obtain a modifier; Step A2: Acrylic acid, acrylamide, acrylonitrile, and DMF are mixed and stirred, and azobisisobutyronitrile is added. After the reaction, a modifying monomer is added and the reaction is continued to obtain pretreated polyacrylic acid. The pretreated acrylic acid, the modifier, chloroplatinic acid, and DMF are mixed and reacted to obtain modified polyacrylic acid. Step A3: Weigh the following raw materials in parts by weight: 3-10 parts of conductive carbon black, 90-97 parts of few-layer graphene, 100-150 parts of modified polyacrylic acid, 3-5 parts of silver powder, 15-30 parts of polyvinyl pyrrolidone and 500-1500 parts of solvent, mix the raw materials evenly, and prepare a carbon-coated aluminum foil conductive coating.
2. The carbon-coated aluminum foil conductive coating according to claim 1, characterized in that: In the preparation of the intermediate 1 described in step A1, the molar ratio of acrylic acid to diethanolamine is 1:1, and in the preparation of the modifier, the molar ratio of the intermediate 1 to thioglycolic acid is 1:
2.
3. The carbon-coated aluminum foil conductive coating according to claim 1, characterized in that: The weight ratio of acrylic acid, acrylamide, acrylonitrile and modified monomer in step A2 is 60-70:20-30:10-15:2-4, and the molar ratio of Si-H bonds on the pretreated acrylic acid and the modifier is 1:
1.
4. The carbon-coated aluminum foil conductive coating according to claim 1, characterized in that: The solvent described in step A3 is a mixture of deionized water and alcohol in any proportion, and the alcohol is a mixture of one or more of ethanol, n-propanol, isopropanol and n-butanol in any proportion.
5. The carbon-coated aluminum foil conductive coating according to claim 1, characterized in that: The modified monomer is prepared by the following steps: Step B1: p-phenylenediamine, allyl alcohol glycidyl ether and DMF are mixed to react to obtain intermediate 2, and intermediate 2, p-nitrophenylboronic acid and DMF are mixed and reacted under nitrogen protection to obtain intermediate 3; Step B2: Intermediate 3, trichlorosilane, chloroplatinic acid, and DMF are uniformly mixed and nitrogen is introduced to react to obtain Intermediate 4. Dimethylhydrogensilanol lithium and DMF are mixed and stirred, and trifluoropropylmethylcyclotrisiloxane is added. After the temperature is raised to react, a modifier is added and the reaction is continued to obtain a modified polysiloxane. Step B3: The modified polysiloxane, zinc powder, deionized water and DMF are mixed and stirred, and concentrated hydrochloric acid is added to react to obtain amino polysiloxane. The amino polysiloxane, p-toluenesulfonic acid, 4A molecular sieve and DMF are mixed and stirred, and cinnamaldehyde is added to react to obtain a modified monomer.
6. The carbon-coated aluminum foil conductive coating according to claim 5, characterized in that: The molar ratio of p-phenylenediamine and allyl alcohol glycidyl ether in step B1 is 1:4, and the molar ratio of intermediate 2 and p-nitrophenylboric acid is 1:
2.
7. The carbon-coated aluminum foil conductive coating according to claim 5, characterized in that: The molar ratio of the intermediate 3 and trichlorosilane in step B2 is 1:4, and the molar ratio of lithium dimethylhydrogensilanol, trifluoropropylmethylcyclotrisiloxane and Si-CI on the intermediate 4 is 1:5:
1.
8. The carbon-coated aluminum foil conductive coating according to claim 5, characterized in that: The modified polysiloxane, zinc powder, deionized water, DMF and concentrated hydrochloric acid described in step B3 are used in a ratio of 152 g:15 g:50 mL:200 mL:50 mL, and the molar ratio of amino group to cinnamaldehyde on the amino polysiloxane is 1:1.